Nutrition and Metabolic Adaptations in Physiological and Complicated Pregnancy: Focus on Obesity and Gestational Diabetes - Parrettini, Sara; Caroli, Antonella; Torlone, Elisabetta (Frontiers in Endocrinology, 2020)
Pregnancy offers a window of opportunity to program the future health of both mothers and offspring. During gestation, women experience a series of physical and metabolic modifications and adaptations, which aim to protect the fetus development and are closely related to both pre-gestational nutritional status and gestational weight gain. Moreover, pre-gestational obesity represents a challenge of treatment, and nowadays there are new evidence as regard its management, especially the adequate weight gain. Recent evidence has highlighted the determinant role of nutritional status and maternal diet on both pregnancy outcomes and long-term risk of chronic diseases, through a transgenerational flow, conceptualized by the Development Origin of Health and Diseases (Dohad) theory. In this review we will analyse the physiological and endocrine adaptation in pregnancy, and the metabolic complications, thus the focal points for nutritional and therapeutic strategies that we must early implement, virtually before conception, to safeguard the health of both mother and progeny. We will summarize the current nutritional recommendations and the use of nutraceuticals in pregnancy, with a focus on the management of pregnancy complicated by obesity and hyperglycemia, assessing the most recent evidence about the effects of ante-natal nutrition on the long-term, on either maternal health or metabolic risk of the offspring.